1996
DOI: 10.1021/jo951188l
|View full text |Cite
|
Sign up to set email alerts
|

Enediynes as Antitumor Compounds:  Synthesis of Tetrahydropyridine Derivatives

Abstract: Enediyne anticancer antibiotics are a rapidly emerging class of compounds derived from natural sources. Many synthetic approaches for the construction of simpler compounds containing this pharmacophore have recently been published. Most of these approaches use the quinoline ring as the heterocyclic moiety . In this paper, we describe a synthetic route for the preparation of enediyne systems 14 and 15, which include in their structure a tetrahydropyridine ring and are related to dynemicin A. Their stereochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Alkenyl and alkynyl Grignard reagents underwent 1,2-addition exclusively (entries 7–9), and addition of alkynyl Grignard reagents to 2-alkylpyridines gave very high levels of 6-selectivity. This feature was applied to the synthesis of piperidine alkaloids (±)-solenopsine A and (±)-monomorine I, as well as to ene–diyne derivatives containing tetrahydropyridine moieties . Other metalloalkynes have been shown to add to N -acyl pyridiniums at the 2-position as the magnesium, silver, or zinc species, or with an amine base in the presence of a catalytic quantity of copper salt. , In all cases, the addition to the 2-position is favored, rather unusually for organocopper species as these reagents are considered as soft nucleophiles.…”
Section: Nucleophilic Addition Of Organometallic Reagents To N-acyl P...mentioning
confidence: 99%
“…Alkenyl and alkynyl Grignard reagents underwent 1,2-addition exclusively (entries 7–9), and addition of alkynyl Grignard reagents to 2-alkylpyridines gave very high levels of 6-selectivity. This feature was applied to the synthesis of piperidine alkaloids (±)-solenopsine A and (±)-monomorine I, as well as to ene–diyne derivatives containing tetrahydropyridine moieties . Other metalloalkynes have been shown to add to N -acyl pyridiniums at the 2-position as the magnesium, silver, or zinc species, or with an amine base in the presence of a catalytic quantity of copper salt. , In all cases, the addition to the 2-position is favored, rather unusually for organocopper species as these reagents are considered as soft nucleophiles.…”
Section: Nucleophilic Addition Of Organometallic Reagents To N-acyl P...mentioning
confidence: 99%
“…In vitro cytotoxic activities of cyclic enediyne isomers 142 were tested against the highly resistant HT-29 human colon carcinoma [102]. They were found to be 100 times less active than amonafide antitumor agent 143.…”
Section: 2mentioning
confidence: 99%
“…From the literature survey, it was found that the hydrazide hydrazone group plays an important role for the anticancer activity [5–9]. On the other hand, a number of dihydropyridine derivatives claimed to possess interesting anticancer activity [10–13]. Also, the importance of the pyridine ring in the chemistry of biological system has greatly realized because of their presence as substructure in many natural products of therapeutic importance, involved in oxidation‐reduction process.…”
Section: Introductionmentioning
confidence: 99%